PENGARUH PENEGAKAN PERATURAN, BUDAYA ETIS ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KECENDERUNGAN KECURANGAN - Anita Primastiwi; Dewi Kusuma Wardhani; Dita Iswahyuni (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2020)
This study aims to examine the effect of enforcement regulations, organizationalethical culture, organizatioal commitment to the tendency of fraud based on fraudtriangle theory in Yogyakarta City Goverment . The data used is primary. Multipleregression analysis is the analytical method used. The sampling technique usedin this study was the purpose sampling method and obtained 83 data samples.The regression test results show that organizational commitment negatively affectthe tendency of fraud in the public sector. Whereas enforcement regulations,organizational ethical culture have on effect the tendency of fraud.